Examining cognition in action: laboratory-based attentional control tasks predict performance on combat-relevant tasks in an augmented reality training environment - Zanesco, Anthony P.; Denkova, Ekaterina; Barry, Jordan; Alessio, Costanza; Jha, Amishi P. (Frontiers in Psychology, 2025)
IntroductionThere is growing interest in understanding how individual differences in cognitive abilities contribute to military performance. Laboratory-based cognitive tasks, which are well-suited for assessing specific cognitive capacities, offer a controlled and efficient approach for evaluating these differences. If performance on such tasks corresponds with operationally relevant performance, these measures could serve as valuable tools for evaluation, selection, and targeted training interventions to enhance military readiness. Here, we examined associations between performance on laboratory tasks of attentional control and operationally relevant tasks in an augmented reality military training environment.MethodsAcross two study rounds, 45 squads of active-duty U.S. Army soldiers (N = 356) completed two laboratory-based tasks of attentional control and a series of operationally relevant drills, requiring attentional control.ResultsSoldiers’ performance on sustained attention and working memory tasks was positively correlated with their performance on operationally relevant drills. Specifically, in both rounds, individuals with greater sustained attention task accuracy performed better on a Shoot/Do Not Shoot drill.ConclusionThe results indicate that laboratory-based attentional control tasks can serve as useful indicators of performance in military operationally relevant drills. Furthermore, these findings suggest that individual differences in attentional control may influence operationally relevant performance.